Liophis dilepis (Lema’s Ground Snake) and Philodryas olfersii latirostris (Lichtenstein’s Green Racer). Bromeliad refugia - Schaefer, Eduardo Federico (2011)
We conducted periodic diurnal surveys to investigate the fauna associated with colonies of  Aechmea distichantha (Bromeliaceae) at El Perichón, 10 km NE of Corrientes City, Argentina, 27.4321111°S, 58.7466111°W, datum: WGS84. The area is included within the Chacoan Domain, Oriental Chaco District, and is characterized by the presence of numerous temporary, semipermanent, and permanent water bodies. The original plant community at the study site was Schinopsis balansae forest, which is currently extremely degraded and largely replaced by sclerophyllous forest with prevalence of Prosopis affinis, P. nigra, Acacia caven, Celtis spp., and numerous colonies of Aechmea distichantha and Bromelia spp. On 1 October 2007, at 1726 h, we found an adult L. dilepis inside an A. distichantha leaf axilla. Six days before, on 27 September 2007, at 1900 h, within another A. disctichantha colony, we discovered an adult P. o. latirostris hidden inside a bromeliad axil. Considering that these snakes were found hidden in evening hours, it is possible that they use the axils of Aechmea distichantha as nocturnal shelter. It is also important to note that bromeliad axils have the capacity to store water for long periods and are used by several amphibian species. Thus, these plants may provide snakes abundant food in addition to shelter.